Nanocomposite CoSb3-type thermoelectric materials - Yan, Fang (2010)
Investigations on high performance thermoelectric materials have recently been an attractive area of research due to the possibility of using these materials for many potential applications in thermoelectric cooling and thermoelectric power generation. This project focused on the study of CoSb3, which is widely used at intermediate temperatures ranging from 500K to 900K. The samples prepared were p-type CoSb3 nanocomposites, comprising of CoSb3 nanoparticles in a micron-sized double filled CoSb3 matrix. The nanopowders were synthesized using a modified polyol method and the micron-sized powders by solid state synthesis method. Nanocomposites with different amount of nanoparticles added were prepared and their thermal conductivities were analyzed using Laser Flash method. The relationship between thermal conductivity and the amount of nanoparticles added was discussed. The results obtained showed that nanostructuring indeed lowers thermal conductivity, with the higher proportion of nanopowder in the sample yielding the lowest thermal conductivity value. It is concluded that with further study on the other properties of the samples, the system can be further optimized to increase the performance of this type of material.